2013
DOI: 10.1177/0020852313478251
|View full text |Cite
|
Sign up to set email alerts
|

Accountability of immigration administration: comparing crises in Norway, Denmark and Germany

Abstract: Accountability can be conceptualized as institutionalized mechanisms obliging actors to explain their conduct to different forums, which can pose questions and impose sanctions. This article analyses different 'crises' in immigration policies in Norway, Denmark and Germany along a descriptive framework of five different accountability types: political, administrative, legal, professional and social accountability. The exchanges of information, debate and their consequences between an actor and a forum are cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The authors concluded that relationships that particularly exists between elected officials, public servants and citizens are not strong and the actor-forum relationships are not achieving the expected outcomes, for instance, citizens are labelled as principal (forum) and elected officials are the agent (actor), however, in practice, citizens are treated as actors and elected officials are treated as principals. On the contrary, a study conducted by Reichersdorfer, Christensen & Vrangbaek (2013) on three developed countries -Norway, Denmark and Germany -of their public sector accountability mechanisms found that accountability relationship between elected officials and citizens and pressure groups are very strong. Internal levels of accountability such as professional accountability were not as strong, however, these parties were answerable when issues were triggered by legal and social/political forums in the accountability relationships such as citizens, pressure groups, legal system.…”
Section: Accountability Systemsmentioning
confidence: 89%
“…The authors concluded that relationships that particularly exists between elected officials, public servants and citizens are not strong and the actor-forum relationships are not achieving the expected outcomes, for instance, citizens are labelled as principal (forum) and elected officials are the agent (actor), however, in practice, citizens are treated as actors and elected officials are treated as principals. On the contrary, a study conducted by Reichersdorfer, Christensen & Vrangbaek (2013) on three developed countries -Norway, Denmark and Germany -of their public sector accountability mechanisms found that accountability relationship between elected officials and citizens and pressure groups are very strong. Internal levels of accountability such as professional accountability were not as strong, however, these parties were answerable when issues were triggered by legal and social/political forums in the accountability relationships such as citizens, pressure groups, legal system.…”
Section: Accountability Systemsmentioning
confidence: 89%
“…Embedded in such context, observers note a tendency in the field of education towards entering accountability-related discussions in a combative and reactive stance (Sahlberg, 2007[55]; Sahlberg, 2010 [56]). In turn, accountability tensions in education are especially prone to serve as 'battlegrounds' for more fundamental stakeholder positions (Reichersdorfer, Christensen and Vrangbaek, 2013 [57]). These well-trodden battlegrounds can produce tensions amongst stakeholders periodically swelling in line with adjustments to respective interests, for example along the lines of reconciling centralised or localised curricula or balancing teacher professional discretion with responsiveness to parental expectations (Jaafar and Anderson, 2007[58]; Cochran-Smith, Piazza and Power, 2013 [59]).…”
Section: More and More Vocal Forumsmentioning
confidence: 99%
“…4-5). At the heart of accountability are information, debate/interaction, and consequence (Reichersdorfer, Christensen, & Vrangbaek, 2013). The accountability-related literature has generated various kinds of typologies, usually using the "accountable to whom" question as device to generate different types of categories (Bovens, 2007;Romzek & Dubnick, 1987;Schillemans, 2008).…”
Section: Social Accountability and Reputation Managementmentioning
confidence: 99%